(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
This article is about Mexico City workers as seen from formal sociability. The chosen year represents, as everybody knows, the final crisis of the “Porfiriato” (the time Porfirio Díaz was the President of Mexico) characterized by a political conflict and certain sectors of the society change. How some workers were inserted into the urban conflict that divided the elite is analyzed as well as their capacity to adopt their leaders’ slogans is evaluated. The article studies the working class through the Mutualist and Moralizing Workers Society and the political associations that organized the workers during the political campaign in 1909-1910.